Low molecular weight heparin does not increase bleeding and mortality post‐endoscopic variceal band ligation in cirrhotic patients. (25th March 2018) - Bianchini, Marcello; Cavani, Giulia; Bonaccorso, Ambra; Turco, Laura; Vizzutti, Francesco; Sartini, Alessandro; Gitto, Stefano; Merighi, Alberto; Banchelli, Federico; Villa, Erica; Schepis, Filippo
Abstract: Background & Aims: Anticoagulants are commonly indicated in cirrhotic patients due to high rate of (pro)thrombotic conditions. Low molecular weight heparin (LMWH) is safe in patients with esophageal varices. However, the safety of LMWH is unknown in patients undergoing prophylactic endoscopic variceal ligation (EVL). To define the 4‐week risk of bleeding and death after prophylactic EVL in cirrhotic patients continuously treated with LMWH. Methods: All EVLs performed at a tertiary Italian Center from 2009 to 2016 were retrospectively reviewed. Patients treated with LMWH were classified as on‐LMWH; the remaining as no‐LMWH. Endoscopic characteristics at first and index EVL (that preceding an endoscopy either showing a bleeding episode or the absence of further treatable varices) and clinical events within 4 weeks from the procedures were recorded. Results and Conclusions: Five hundred fifty‐three EVLs were performed in 265 patients (in 215 as a primary prophylaxis): 169 EVLs in 80 on‐LMWH and 384 in 185 no‐LMWH (4.9 ± 1.1 vs 4.8 ± 1.0 bands/session, respectively; P = .796). Six patients bled (2.2%) without between‐groups difference (3.8% on‐LMWH vs 1.6% no‐LMWH, Log‐rank P = .291). Large varices with red marks (100% vs 51.4%, P = .032), number of bands (5.6 ± 0.5 vs 4.6 ± 1.2, P = .004), underlying portal vein thrombosis (66.7% vs 23.6%, P = .033), and creatinine (2.2 ± 2.7 vs 1.0 ± 0.8 mg/dL, P = .001) at index EVL were significantly different between bleeders and non‐bleeders. Six patients died within 4‐week from index EVL, without between‐groups difference (2.5% on‐LMWH vs 2.2% no‐LMWH, Log‐rank P = .863). LMWH does not increase the risk of post‐procedural bleeding and does not affect survival of cirrhotic patients undergoing prophylactic EVL. Abstract : See Editorial on Page1175